Insulin-like growth factor 1 triggers salt secretion machinery in fish under acute salinity stress. Issue 3 (September 2020) - Yan, Jia-Jiun; Lee, Yi-Chun; Tsou, Yi-Ling; Tseng, Yung-Che; Hwang, Pung-Pung
Abstract : Timely adjustment of osmoregulation upon acute salinity stress is essential for the survival of euryhaline fish. This rapid response is thought to be tightly controlled by hormones; however, there are still questions unanswered. In this work, we tested the hypothesis that the endocrine hormone, insulin-like growth factor 1 (Igf1), a slow-acting hormone, is involved in the activation of salt secretion mechanisms in euryhaline medaka ( Oryzias melastigma ) during acclimation to acute salinity stress. In response to a 30-ppt seawater (SW) challenge, Na + /Cl − secretion was enhanced within 0.5 h, with concomitant organization of ionocyte multicellular complexes and without changes in expression of major transporters. Igf1 receptor inhibitors significantly impair the Na + /Cl − secretion and ionocyte multicellular complex responses without affecting transporter expression. Thus, Igf1 may activate salt secretion as part of the teleost response to acute salinity stress by exerting effects on transporter function and enhancing the formation of ionocyte multicellular complexes. These findings provide new insights into hormonal control of body fluid ionic/osmotic homeostasis during vertebrate evolution.